English as Symbolic Capital: Globalization and the Linguistic Landscape of Armenia, Quindío (Colombia) - Daniel Guarín; Diego Arias-Cortés (Languages)
This research investigates linguistic hybridization in a commercial corridor of Armenia, Colombia, focusing on the usage of Spanish and English in public signage, particularly business names. Utilizing a quantitative methodology, we conducted a statistical analysis employing Chi-square tests to explore the relationship between symbolic language choice and variables such as location and type of establishment. The results demonstrated a significant association between location and language choice (Χ2 = 39.353, p < .001), revealing that commercial zones with high tourist traffic exhibited a pronounced preference for English (46.55%), reflecting branding strategies aimed at attracting a younger, cosmopolitan audience. Conversely, traditional sectors such as health services (74.24% in Spanish) and religious institutions (80% in Spanish) predominantly utilized Spanish, emphasizing the community’s need for accessible communication. Additionally, establishments in the most commercial area highlighted the presence of hybrid names, indicating a blending of languages. Our findings suggest that the hybridization of English and Spanish serves as both a reflection and reinforcement of cultural identity and social hierarchies, emphasizing the role of linguistic capital in shaping social dynamics within the urban landscape of Armenia, Colombia.